Decomposition of triangles into isosceles triangles II: complete solution of the problem by using a computer - Kosztolányi, József; Kovács, Zoltán; Nagy, Erzsébet (Teaching Mathematics and Computer Science, 2004)
We solve an open decomposition problem in elementary geometry using pure mathematics and a computer programme, utilizing a computer algebra system.